Association of ALDH(2) genotypes and alcohol consumption with periodontitis - Nishida, N; Tanaka, M; Hayashi, N; Nagata, H; Takeshita, T; Nakayama, K; Morimoto, K; Shizukuishi, S (Journal of dental research, 2004)
There is little information regarding the association between alcohol consumption and periodontitis risk. We assessed whether alcohol consumption and ALDH(2) genotypes were associated with periodontitis. Subjects' lifestyle was examined by a self-administered questionnaire, and the percentage of pocket depths > or = 3.5 mm was used as a periodontal parameter. ALDH(2) genotypes were determined with the use of a PCR/RFLP method. Multiple logistic analyses showed that alcohol consumption was significantly associated with periodontitis, and its odds ratio was 1.98. There was no significant relationship between periodontal status and ALDH(2) genotypes. However, ALDH(2)*1/*2 subjects who consumed > or = 33 g/day of alcohol had a significantly greater percentage of pocket depths > or = 3.5 mm than those whose daily consumption was lower, while there was no significant difference in periodontal status associated with alcohol consumption in ALDH(2)*1/*1 subjects. Our results suggest that alcohol consumption may be a risk indicator for periodontitis in ALDH(2)*1/*2 subjects who consume larger amounts of alcohol.